PHYTOCHEMICAL SCREENING AND TLC PROFILING OF DIFFERENT EXTRACTS OF LEAVES, ROOTS AND STEM OF ACONITUM HETEROPHYLLUM A RARE MEDICINAL PLANT OF HIMALAYAN REGION - KAMRAJ SINGH; SURABHI SALONI; SHALINI (International Journal of Pharma and Bio Sciences, 2015)
Aconitum heterophyllum plants were studied for the presence of phytochemicals. Methanol extracts of leaves, roots and stems show the presence of corresponding phytochemicals like alkaloids, carbohydrates, protein, amino acid, cardiac glycosides, phenols, flavonoids, saponins, terpenoids and quinones. However the leaves, roots and stem methanol extracts do not shows the presence of Glycosides.TLC profiling of all plant extracts also give an idea about the presence of these phytochemicals. Rf (Retention factor) value of different phytochemicals provide valuable clue regarding their polarity and selection of solvents for separation of phytochemicals.